The relationship of trust in the principal and servant leadership's interaction with work engagement and teacher passion: a multilevel moderated mediation analysis - Uslukaya, Alper; Demirtas, Zulfu; Alanoglu, Muslim (Springer, 2024)
This study aims to analyze a multilevel moderating mediation model to test the mediating role of work engagement in the relationship between trust in the principal and teacher passion and the moderating role of servant leadership by using the motivational pathway of the Job Demands-Resources (JD-R) Model. Using data from a sample of 805 teachers in 51 schools, the study employs multilevel structural equation modeling (MSEM) with a Bayesian estimator to examine the structural relationships between the collective constructs of schools, such as trust in principal, passion for work, servant leadership, and teacher passion. The results show that trust in the principal indirectly correlates with teacher passion by promoting work engagement. The current study also reveals that the indirect relationship between trust in the principal and teacher passion through work engagement depends on the level of servant leadership. We conclude by offering various suggestions for school administrators.
Keywords: Trust in principal; Servant leadership; Work engagement; Teacher passion